2009
DOI: 10.2298/zmspn0917079m
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins as a risk in the grain food

Abstract: Mycotoxins are toxic secondary metabolites of fungi that contaminate a large variety of foods and have toxic effects on humans. The best protection against mycotoxins is to monitor their presence in food. This paper shows the screening results of mycotoxins present in 76 samples of different groups of grain foods. Samples of grain food were analyzed for contamination with aflatoxins, ochratoxin A, zearalenone, fumonisins and deoxynivalenol. Analysis were conducted using competitive enzyme-linked immunosorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
0
11
1
Order By: Relevance
“…This probably provides a rationale on why only a few studies of AFs occurrence were conducted in Serbia prior to 2012. Furthermore, those studies have shown no or a low amount of AFs in various food and feed commodities [29,30,31,32,33,34,35,36,37,38]. However, in 2012 Serbia had prolonged drought during spring and summer which might have contributed to the high contamination frequency and concentration of AFs in maize and consequently in milk and dairy products.…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 99%
See 1 more Smart Citation
“…This probably provides a rationale on why only a few studies of AFs occurrence were conducted in Serbia prior to 2012. Furthermore, those studies have shown no or a low amount of AFs in various food and feed commodities [29,30,31,32,33,34,35,36,37,38]. However, in 2012 Serbia had prolonged drought during spring and summer which might have contributed to the high contamination frequency and concentration of AFs in maize and consequently in milk and dairy products.…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 99%
“…Among the products analysed in 2012 and in prior years, AFs were most frequently found in maize and maize-based products. Maize and maize-based products samples analysed prior to 2012 had an AFs prevalence of 9.7% ( n = 351) with none of the samples exceeding the EU MRL [30,31,32,36,37,38]. The samples analysed in 2012 had an AFs prevalence of 49.9% ( n = 724), with 33% of the samples exceeding the EU MRL and with the mean values ranging from 18.15 µg kg –1 to 36.3 µg kg −1 [37,41,42,43,44].…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 99%
“…Wheat (30), barley (20), oats (20), maize (40) and rye (20) samples were collected immediately after the harvest 2012 from the main cereals growing areas in Serbia. Sampling was performed according to EU requirements (European Commission, 2006a) in order to overcome uneven mycotoxins distribution among the crops and kernels.…”
Section: Samplesmentioning
confidence: 99%
“…3,4 Since AFs mainly occur in tropical and subtropical regions where temperature and humidity are favorable for the growth of Aspergillus species and production of the toxins, 5 the greatest numbers of published studies regarding AFs occurrence are from Mediterranean and Middle East regions. 6 Even though environmental conditions in Serbia in previous decade were not favorable for Aspergillus growth and AFs production, 7,8 changes in weather conditions in Serbia during year 2012 had a great influence on the occurrence of AFs in maize 9,10 and AFM1 in milk samples. 11 Determined concentrations of AFM1 in milk samples was very high and risk assessment analysis showed that all age categories, especially children, are exposed with high risk related to presence of AFM1 in milk.…”
Section: Introductionmentioning
confidence: 99%